A solution proposal for car parking problems in cities: “Neighbourhood car parking cooperatives” - (:unkn) unknown (Peter Lang Publishing Group, 2019)
Solidarity has always been a core agenda of human beings. When we lack power, we seek the assistance of a partner with common objectives. It has been the solution in solving problems. Here, cooperatives are the reflection of such consciousness focusing on unity and solidarity. There is no tissue incompatibility between a human being and a cooperation because cooperatives are totally compatible with human nature and values. That is why they are as old concept as the history of humankind, and they have been a social behaviour model in history. Cooperatives are strategic organisations formed on the basis of a synergetic partnership approach; partaker, participator and solidarity, responding to all kinds of needs and requests including today and tomorrow of a community, offering quality products and services using the resources in a transparent and rational way on the basis of effectiveness, and finally predominantly focusing on human happiness and hence no doubly targeting sustainable development (Mori, 2014:330; Picciotti, 2014:214; Ifenkwe, 2012:21; Zaimova et al., 2012:52; Segu’i-Mas, 2015:365; Casaburi, 2015:286; Verhees et al., 2015:42). Kanli (2016:4) also claims that “Co-operatives are not enterprises that have only economic objectives but they also have social and cultural objectives using democratic principles in order to establish a new generation social order.” According to International Co-operative Alliance (ICA) (www.ica.coop, 2018): “A co-operative is an autonomous association of persons united voluntarily to meet their common economic, social, and cultural needs. © Peter Lang GmbH Internationaler Verlag der Wissenschaften Berlin 2019 All rights reserved.